2013
DOI: 10.1097/mbc.0b013e32835cc193
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and fibrin clot strength measured by thrombelastography after coronary stenting

Abstract: Inflammation is implicated in the progression of coronary artery disease and the molecular processes of inflammation and thrombosis are closely intertwined. Elevated levels of C-reactive protein (CRP) have been associated with an elevated risk of adverse ischaemic events after coronary stenting and hypercoagulability. Heightened whole blood clot strength measured by thrombelastography (TEG) has been associated with adverse ischaemic events after stenting. We intended to examine the relationship of CRP to plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
3
15
1
Order By: Relevance
“…As previously shown in subjects with stable coronary artery disease undergoing PCI, CRP levels also correlated with plasma fibrin clot strength in patients with NSTEMI in our study (9). …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As previously shown in subjects with stable coronary artery disease undergoing PCI, CRP levels also correlated with plasma fibrin clot strength in patients with NSTEMI in our study (9). …”
Section: Discussionsupporting
confidence: 89%
“…Both plasma fibrinogen and C-reactive protein were measured by commercially available ELISA as previously described (9). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, platelets have relevant functions in inflammation and it has been shown that thrombosis and inflammation share several key molecular mechanisms and linked processes [23]. Similarly, MPV has been investigated in connection with both thrombosis and inflammation [24] and elevated CRP may be linked to procoagulant changes and high tensile fibrin clot strength independent of fibrinogen concentration [25]. This may favor the deleterious process of plaque vulnerability and thrombus formation [26] which may explain also the higher incidence of thrombosis complications seen in hypoxemic CHD patients.…”
Section: Discussionmentioning
confidence: 98%
“…During acute coronary syndromes (ACS), activation of coagulation and thrombin generation is a central step preceding coronary thrombosis and treatment with heparin or low molecular weight heparin is standard of care in the initial in-hospital management of ACS [4]. Risk associated with continued prothrombotic changes related to vascular inflammation may be an important mediator of long term recurrent risk of ischemic events in patients with coronary stenting [510]. While large scale efforts have been directed at identifying genetic variants causally linked to the development of coronary artery disease, fewer efforts have been directed specifically at identifying single nucleotide polymorphisms (SNPs) associated with recurrent ischemic risk in patients with established coronary artery disease [11].…”
Section: Introductionmentioning
confidence: 99%